DAMPAK PANDEMI EKONOMI COVID-19 PADA PASAR MODAL - Pakihatun; Pocut Ainiah; Juwanda (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2026)
The Covid-19 pandemic has had a profound impact on global and national economies, including the Islamic capital market in Indonesia. This study analyzes the effects of the pandemic on the Islamic stock market by examining key indices such as the Jakarta Islamic Index (JII) and the Indonesia Sharia Stock Index (ISSI), as well as Islamic financial instruments like sukuk and sharia mutual funds. Using a qualitative approach with document analysis method, this research systematically examines official reports from the Indonesia Stock Exchange, regulations from the Financial Services Authority (OJK), and relevant scientific publications to understand the pandemic's impact comprehensively. The findings reveal that the pandemic triggered significant volatility in stock prices, trading volume, and market liquidity, with JII reaching its lowest point at 476.39 points in March 2020. However, Islamic capital markets showed relatively greater resilience compared to conventional markets, with lower decline rates in market capitalization (22.4%) and performance (16.3%) compared to conventional markets. This resilience stems from adherence to sharia principles that prohibit excessive speculation and interest-based transactions. The research highlights the stability of sukuk and sharia mutual funds amid the crisis and the growing interest from investors in ethical and halal investment options during uncertain economic times. This research provides insights into the risk management and sustainability of Islamic finance during global economic shocks and offers recommendations for market participants and regulators to strengthen the resilience and growth of the Islamic capital market.